Comparative Efficacy of Chinese Herbal Injections Combined with Paclitaxel Plus Cisplatin for Non-Small-Cell Lung Cancer: A Multidimensional Bayesian Network Meta-Analysis. (29th October 2020) - Ni, Mengwei; Wang, Haojia; Wang, Miaomiao; Zhou, Wei; Wu, Jiarui; Sun, Bin; Zhang, Qianqian; Fan, Xiaotian; Zhang, Dan; Jing, Zhiwei; Zhang, Jingyuan; Liu, Xinkui; et al.
Abstract : Introduction . Considering the limitations of pure paclitaxel plus cisplatin chemotherapy in the treatment of non-small-cell lung cancer and the extensive exploration of Chinese herbal injections, this study performed a multidimensional network meta-analysis to systematically evaluate the clinical efficacy and safety of 12 Chinese herbal injections in the treatment of non-small-cell lung cancer. Methods . Randomized controlled trials were obtained from several databases according to the eligibility criteria, and the study quality was assessed by the Cochrane risk of bias tool. Data analysis was performed by Stata 13.1 software and WinBUGS 14.0 software. Multidimensional cluster analysis was performed with the "scatterplot3d" package in R 3.6.1 software (PROSPERO ID: CRD42020163503). Results . A total of 58 eligible randomized controlled trials involving 4578 patients and 12 Chinese herbal injections were included. Combined with paclitaxel plus cisplatin chemotherapy, Xiaoaiping injection exhibited a better impact on the clinical effective rate than paclitaxel plus cisplatin alone. Shenqifuzheng injection was associated with a preferable response in performance status and reduced leukopenia and gastrointestinal reactions. Kangai injection was dominant in the comprehensive results of the cluster analysis. Conclusions . Chinese herbal injections combined with paclitaxel plus cisplatin chemotherapy have a certain adjuvant effect in treating non-small-cell lung cancer, but the results of this study need to be verified by more well-designed, large-sample, multicenter randomized controlled trials.